Teacher perception on the use of e-portfolio as formative assessment for pre-service teacher in English department - Aulia Oktri Syafila (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2020)
The aim of this research is to explore how the teacher’s perception of the use e-Portfolio as formative assessment for Pre-service teachers. The setting of this research was in English Department study program in a higher education. The participant in this research are 3 lecturers. The participants are lecturers of one university in Yogyakarta who teach in microteaching class. The research design is a qualitative method, which specifically employed thematic analysis thematic analysis. The researcher chose a thematic analysis research design because this type of research will facilitate the researcher in exploring and describing teachers’ perception uses e-Portfolio as formative assessment in their class with their students. The data were collected through interviews involving the lectures assigned in higher education in Yogyakarta. The most types applied by the participant were in terms of recognition and aggression. An appealing finding was found that the use of e-Portfolio as a formative assessment in the classroom are very helpful and facilitate the teacher in the learning process. Keywords: e-Portfolio, Formative assessment; Teachers’ perception; Pre-Service Teachers